(untitled) (Research, Society and Development, 2022)
Accounting undergraduate students’ lack of knowledge about tax matters and the confusion they make about Tax Accounting is a growing reality in higher education. Studies indicate that a motivated student tends to give greater importance to the content learned and thus has a greater interest in capturing the subject. Assuming the relevance of tax accounting in the training of the accounting professional, it would then show, to the future accounting professional, greater skill in tax treatment. Thus, the objective of this study is to analyze the perception of students of the Accounting Sciences course on the importance of knowledge in tax accounting for their training. For evidence collection, quantitative research was used through non-probabilistic sampling and, the application of a questionnaire prepared on the Google Forms® platform, and applied to academics and graduates of a Higher Education Institution in Manaus-AM. With a total of 29 responses, the analysis indicated that students believe that tax accounting knowledge is sufficiently provided at the IES. It is evident that this research can contribute to the students and professors of the Accounting Sciences course, in order to provide a more in-depth view of the main and most recurrent competencies of the accounting professional, allowing the professors to offer more effective teaching in the formation of their students and also to serve as a facilitator for students to more confidently define their area of specialization, based on the requirements of the job market.